Survival after allogeneic transplantation according to pretransplant minimal residual disease and conditioning intensity in patients with acute myeloid leukemia - Núñez-Torrón Stock, Claudia; Jiménez Chillón, Carlos; Martín Moro, Fernando; Marquet Palomanes, Juan; Piris Villaespesa, Miguel; Roldán Santiago, Ernesto; Rodríguez Martín, Eulalia; Chinea Rodríguez, Anabelle; García Gutiérrez, Valentín; Moreno Jiménez, Gemma; López Jiménez, Javier; Herrera Puente, Pilar (Frontiers in Oncology, 2024)
Background: The measurement of minimal residual disease (MRD) by multiparametric flow cytometry (MFC) before haematopoietic stem cell transplantation (HSCT) in patients with acute myeloid leukaemia (AML) is a powerful prognostic factor. The interaction of pretransplant MRD and the conditioning intensity has not yet been clarified. Objective: To analyze the transplant outcomes of patients with AML who underwent HSCT in complete remission (CR), comparing patients with positive MRD (MRD+) and negative MRD (MRD-) before HSCT and the interaction between conditioning intensity and pre-HSCT MRD. Study design: We retrospectively analyzed the transplant outcomes of 118 patients with AML who underwent HSCT in complete remission in a single institution, comparing patients with MRD+ and MRD- before HSCT using a cut-off of 0.1% on MFC, and the interaction between conditioning intensity and pre-HSCT MRD. Results: Patients with MRD+ before HSCT had a significantly worse 2-year (2y) event-free survival (EFS) (56.5% vs 32.0%, p = 0.018) than MRD- patients, due to a higher cumulative incidence of relapse (CIR) at 2 years (49.0% vs 18.0%, p = 0.002), with no differences in transplant-related mortality (TRM) (2y-TRM 19.0% and 25.0% respectively, p = 0.588). In the analysis stratified by conditioning intensity, in patients who received MAC, those with MRD- before HSCT had better EFS (p = 0.009) and OS (p = 0.070) due to lower CIR (p = 0.004) than MRD+ patients. On the other hand, the survival was similar in RIC patients regardless MRD status. Conclusions: Patients with MRD+ before HSCT have worse outcomes than MRD- patients. In patients who received MAC, MRD- patients have better EFS OS due to lower CIR than MRD+ patients, probably because they represent a more chemo sensitive group. However, among RIC patients results where similar regardless MRD status.